Nikah Siri Pasca KUHP Baru: Analisis Hukum Islam dan Hukum Positif - Muhammad Arafat; Rizki Mulyaningsih (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2026)
This article examines the legal position of nikah siri after the enactment of Indonesia’s new Criminal Code by analyzing its relation to Islamic law and national normative law. Nikah siri remains a recurring phenomenon in Indonesian Muslim society because it is often considered valid from a religious perspective when it fulfills the pillars and requirements of marriage, but it is not recorded by the state. This condition creates legal uncertainty, especially after the regulation of adultery and cohabitation in Articles 411 and 412 of the new Criminal Code. This study uses normative legal research with statutory, conceptual, and Islamic legal approaches. The legal materials are analyzed qualitatively and prescriptively to assess the relationship between religious validity, marriage registration, and criminal law interpretation. The findings show that nikah siri cannot automatically be equated with adultery or cohabitation when it is based on a valid Islamic marriage contract. However, the absence of official registration weakens the evidentiary position of the spouses and may create vulnerability in proving marital status before law enforcement authorities. From the perspective of maqāṣid al-syarī‘ah, marriage registration is not merely an administrative requirement, but a legal instrument to protect lineage, property, honor, women, and children. This article argues for a proportional legal construction that rejects the automatic criminalization of nikah siri while strengthening marriage registration and isbat nikah as mechanisms for family legal protection.